Psychological treatment of traumatic memories in COVID‐19 survivors. (29th August 2022) - Dinapoli, Loredana; Ferrarese, Daniele; Belella, Daniela; Carnevale, Stefania; Camardese, Giovanni; Sani, Gabriele; Chieffo, Daniela Pia Rosaria
Abstract: The COVID‐19 pandemic, which has affected a significant number of individuals worldwide, is generating serious mental health issues. Recovered COVID‐19 patients have experienced traumatic events related to their symptoms, isolation, possible hospitalization, bereavement, fear of infecting loved ones and the physical consequences of COVID‐19. One effective psychological treatment for these patients is Eye Movement Desensitization and Reprocessing (EMDR). The aim of this paper is to describe the therapeutic intervention and effects of EMDR in a pool of COVID‐19 survivors referred to an integrated psychological/psychiatric outpatient service. Twelve patients, comprising of nine males and three females, underwent EMDR psychotherapy from October 2020 to February 2022. Each patient received 8–16 weekly treatment sessions. The standard EMDR protocol of eight stages was administered to enable desensitization and reprocessing of four main targets: first positive swab, hospitalization, isolation and fear for relatives' health. Efficacy of EMDR was demonstrated by the significant improvement at clinical scale for subjective distress caused by traumatic events. For the therapists, carrying out these treatments was an intense and challenging experience. In fact, the perceived distance between therapist and patient was less defined than in other hospital settings because the pandemic affects everyone equally. However, with the widespread availability of vaccines and although the pandemic is still ongoing with the emergence of new variants, a window of improvement in the mental health landscape is starting to open up.